2021
DOI: 10.1007/s11255-021-02996-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of lymph node ratio in comparison to positive lymph node count in penile squamous cell carcinoma

Abstract: Purpose Penile cancer is a rare male neoplasm with a wide variation in its global incidence. In this study, the prognostic value of lymph node ratio (LNR) was compared to that of positive lymph node count (PLNC) in penile squamous cell carcinoma. Methods A total of 249 patients with penile squamous cell carcinoma were enrolled from The Surveillance, Epidemiology, and End Results (SEER) database between 2010 and 2015. The X-tile program was used to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…From the Memorial Sloan–Kettering Cancer Center surgical database between January 1995 and September 2011, the 3-year CSS rates of patients with positive, negative, and unknown LNM status were 90%, 65%, and 86%, respectively ( p = 0.03) [ 18 ]. Previous studies of the prognosis of PSCC demonstrated that the histopathological characteristics of inguinal LNs, including the number of positive nodes, LN density, and PLNM, are predictive factors associated with CSS [ 8 , 18 , 19 , 20 , 21 , 22 ]. Based on the report from the Istituto Nazionale Tumori, the LN ratio (LNR) was an important prognostic parameter in a contemporary population of patients who underwent surgical treatment for PSCC and LNM [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the Memorial Sloan–Kettering Cancer Center surgical database between January 1995 and September 2011, the 3-year CSS rates of patients with positive, negative, and unknown LNM status were 90%, 65%, and 86%, respectively ( p = 0.03) [ 18 ]. Previous studies of the prognosis of PSCC demonstrated that the histopathological characteristics of inguinal LNs, including the number of positive nodes, LN density, and PLNM, are predictive factors associated with CSS [ 8 , 18 , 19 , 20 , 21 , 22 ]. Based on the report from the Istituto Nazionale Tumori, the LN ratio (LNR) was an important prognostic parameter in a contemporary population of patients who underwent surgical treatment for PSCC and LNM [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PSCC with an LN density >20% had an increased risk of recurrence or progression in the univariate (hazard ratio (HR), 2.12; 95% confidence interval (CI), 1.18–3.80; p = 0.011) and multivariate (HR, 2.32; 95% CI, 1.21–4.45; p = 0.011) analyses [ 19 ]. Yu et al reported that the CSS of patients with PSCC with an LNR >0.23% was significantly worse than that of those with an LNR ≤0.23% [ 20 ]. However, positive lymph node count (PLNC) was not associated with CSS in the multivariate analysis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations